Selective Pharmacological Inhibition of NOX2 by GSK2795039 Improves Bladder Dysfunction in Cyclophosphamide-Induced Cystitis in Mice - Mariana G. de Oliveira; Fabíola Z. Monica; Gabriela R. Passos; Jamaira A. Victorio; Ana Paula Davel; Anna Lethicia Lima Oliveira; Carlos A. Parada; Carlos A. L. D'Ancona; Warren G. Hill; Edson Antunes (MDPI AG, 2022)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic inflammatory disease without consistently effective treatment. Among the many mediators implicated in cystitis, the overproduction of reactive oxygen species (ROS) seems to play a key role, although the main source of ROS remains unclear. This study aimed to investigate the contribution of NADPH oxidase (NOX) isoforms in ROS generation and the voiding dysfunction of cyclophosphamide (CYP, 300 mg/Kg, ip, 24 h)-induced cystitis in adult female mice, a well-recognized animal model to study IC/BPS, by using GKT137831 (5 mg/Kg, ip, three times in a 24 h period) or GSK2795039 (5 mg/Kg, ip, three times in a 24 h period) to inhibit NOX1/4 or NOX2, respectively. Our results showed that treatment with GSK2795039 improved the dysfunctional voiding behavior induced by CYP, reduced bladder edema and inflammation, and preserved the urothelial barrier integrity and tight junction occludin expression, besides inhibiting the characteristic vesical pain and bladder superoxide anion generation. In contrast, the NOX1/4 inhibitor GKT137831 had no significant protective effects. Taken together, our in vivo and ex vivo data demonstrate that NOX2 is possibly the main source of ROS observed in cystitis-induced CYP in mice. Therefore, selective inhibition of NOX2 by GSK2795039 may be a promising target for future therapies for IC/BPS.